RESILIENSI BUDAYA TOLERANSI BERAGAMA MASYARAKAT MULTIKULTURAL DI KABUPATEN BURU - Susiati Susiati; Sumiaty Sumiaty; La Husni Buton (Harmoni, 2022)
The objectives of this study are 1) to describe the pattern of cultural resilience of religious tolerance in the multicultural community in Buru Regency; 2) identify the factors that influence the cultural resilience of religious tolerance in the multicultural community in Buru Regency. This type of research is descriptive qualitative with a phenomenological approach. The theory used to see patterns of cultural resilience of religious tolerance in multicultural society in Buru Regency, namely the theory of Wagnil and Young, while to identify the factors for the emergence of cultural resilience of religious tolerance in multicultural society in Buru Regency, Reivich and Shatte theory are used. Data obtained from primary data and secondary data. The location of this research is in Namlea Village, Namlea District, Buru Regency. The method of data collection in this study is the observation method with the techniques used, namely field surveys (field studies), interviews (interviews), documentation studies, and literature studies.The results showed that the cultural resilience pattern of religious tolerance in the multicultural community in Buru Regency, especially in the Namlea community, focused on five aspects of resilience, namely Meaningful Life (purpose); Perseverance; Equanimity; Sell-reliance; Coming home to your self. These five aspects gave birth to patterns of cultural resilience of religious tolerance in the multicultural community in Buru Regency, especially for the Namlea community, such as fostering an attitude of tolerance, mutual respect, mutual respect, helping each other, building intimacy, and helping each other for the sake of a safe, comfortable, peaceful life. , and prosper. While the factors that influence the emergence of cultural resilience of religious tolerance in multicultural communities in Buru Regency, namely the protective factor in which the Namlea community, Buru Regency has a positive self-concept of attitudes, behavior, perceptions to be applied in the community environment. This support is obtained from the family environment, school environment, community environment.